The Effect of Shading Device and Natural Ventilation on Thermal Comfort in Office Buildings - Sanaye, Kimia (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Window opening ratios have bigger role on thermal comfort conditions of buildings than size and type of fixed external shading devices. In this study, author analyzed an office with standard envelope, by using EDSL Tas software with PMV and PPD results according to thermal sensations of ASHRAE, ISO 7730: 2005 and EN 15251: 2007 for generating the effect by window opening ratio and size of horizontal shading device which affect thermal comfort in Mediterranean climate conditions of Famagusta region. The building which dynamic thermal simulations have been done for it, is oriented on east to west because of the best wind availability. PMV and PPD results showed that thermal comfort is affected by window opening ratios. Annual averaged PMV performance of the simulated office is based on the office hours, this paper shows; 30 cm long with or without any horizontal shading device, when the window is 0% (closed) open PMV is -0.34. When window is 25% open, PMV is -0.25. When window is 50% open (half), PMV is -0.21. When window is 75% open, PMV is -0.2 and when window is 100% (full) open PMV is -0.19. Moreover, according to category A, when PMV is -0.2 to 0.2, averaged yearly thermal comfort based on office hours obtained is approximately 326 hours of all year, according to category B, when PMV is -0.5 to 0.5, averaged yearly thermal comfort obtained is approximately 742 hours of all year and according to category C, when PMV is -0.7 to 0.7, averaged yearly thermal comfort obtained is 915 hours of all year. Keywords: Fixed shading devices, Mediterranean climate, PMV and PPD, ISO, EDSL Tas Software, Thermal comfort.

ÖZ: Pencere açma oranları, binalardaki termal konfor koşullarında, sabit dış gölgeleme cihazlarının boyut ve tiplerine göre daha önemli bir role sahiptir. Bu çalışmada, yazar, pencere açma oranı ve yatay boyut ile efekti elde etmek için, ASHRAE, ISO 7730: 2005 ve EN 15251: 2007 tarihli termik sansasyonlara göre PMV ve PPD sonuçları olan EDSL Tas programı kullanarak standart bir ofisiö Gazimağusa bölgesi ve Akdeniz iklim koşullarında termal konforu etkileyen gölgelendirme cihazı analiz etmiştir. Bunun için dinamik termik simülasyonlar yapılan bina, en iyi rüzgar verimi nedeniyle doğudan batıya doğru yönlendirilir. PMV ve PPD sonuçları, termal konforun pencere açma oranlarından etkilendiğini ortaya koymuştur. Bu araştırma, simülasyon bürosunun yıllık ortalama PMV performansını mesai saatlerine dayanmaktadır; 30 cm uzunluğunda veya yatay bir gölgeleme aygıtı olsun veya olmasın, pencere % 0 olduğunda (kapalı) açık PMV - 0.34'tür. Pencere % 25 açık olduğunda, PMV -0.25'tir. Pencere % 50 açık (yarısı) olduğunda, PMV -0.21'dir. Pencere % 75 açık olduğunda, PMV -0.2 ve pencere % 100 (tam) olduğunda PMV -0.19'dur. Ayrıca, kategori A'ya göre, PMV -0,2 ile 0,2 arasında olduğunda, elde edilen çalışma saatlerine dayalı yıllık ortalama ısıl konfor, yılın yaklaşık 326 saati, kategori B'ye göre, PMV -0,5 ila 0,5 olduğunda ortalama yıllık ısıl konfor elde edilmiştir Tüm yılın yaklaşık 742 saati ve kategori C'ye göre, PMV -0.7 ila 0.7 olduğunda, elde edilen yıllık termal konfor, tüm yılın 915 saatidir. Anahtar Kelimeler: Sabit gölgelendirme elemanları, Akdeniz iklimi, PMV ve PPD, ISO, EDSL Tas programı, Termal konfor.
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2017. Supervisor: Assoc. Prof. Dr. Halil Zafer Alibaba.
Keywords: Architecture; Natural ventilation; Natural ventilation-Office buildings; Buildings-Environmental engineering; Buildings-Thermal properties-Architecture and climate.; Atrium; Thermal Comfort; Building Problem in Hot Humid Climate; TAS Software; Energy Saving